2011
DOI: 10.4103/2045-8932.83447
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Ca2+‐Activated Cl Channels Contributes to Regulating Receptor‐ and Store‐Operated Ca2+ Entry in Human Pulmonary Artery Smooth Muscle Cells

Abstract: Intracellular Ca2+ plays a fundamental role in regulating cell functions in pulmonary arterial smooth muscle cells (PASMCs). A rise in cytosolic Ca2+ concentration ([Ca2+]cyt) triggers pulmonary vasoconstriction and stimulates PASMC proliferation. [Ca2+]cyt is increased mainly by Ca2+ release from intracellular stores and Ca2+ influx through plasmalemmal Ca2+-permeable channels. Given the high concentration of intracellular Cl- in PASMCs, Ca2+-activated Cl-(ClCa) channels play an important role in regulating m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 56 publications
(107 reference statements)
7
34
0
Order By: Relevance
“…5C). These data are in agreement with reported biophysical properties of Ca 2ϩ -activated Cl Ϫ channels in native cells and heterologous expression systems (4,(32)(33)(34)(35) and are consistent with a previous report that CLCA1 modulates the activity of endogenous CaCCs in HEK293T cells (9). In cells transfected with CLCA1 variants, in which the metalloprotease activity was abolished (H156A, E157Q) or in which the cleavage site was disrupted (contra), the gluconate-sensitive currents were markedly decreased (Fig.…”
Section: Biophysical Characterization Of Clca Protease Activity-supporting
confidence: 93%
“…5C). These data are in agreement with reported biophysical properties of Ca 2ϩ -activated Cl Ϫ channels in native cells and heterologous expression systems (4,(32)(33)(34)(35) and are consistent with a previous report that CLCA1 modulates the activity of endogenous CaCCs in HEK293T cells (9). In cells transfected with CLCA1 variants, in which the metalloprotease activity was abolished (H156A, E157Q) or in which the cleavage site was disrupted (contra), the gluconate-sensitive currents were markedly decreased (Fig.…”
Section: Biophysical Characterization Of Clca Protease Activity-supporting
confidence: 93%
“…Consistent with the effects of NFA on SOCE and ROCE in human PA myocytes, 239 we also observed a significant relaxation by the TMEM16A inhibitor T16A Inh -A01 of small intralobar rat pulmonary arteries exposed to CPA and nifedipine. This then leads to the following questions: Is E Cl stable and lying where expected (approx.…”
Section: +supporting
confidence: 87%
“…This result was surprising because aggressive cancer cells would be expected to show stronger Ca 2ϩ signaling intensity in consideration of sustained proliferation and migration. Although it has been demonstrated in proliferative pulmonary artery smooth muscle cells that enhanced SOCE promotes cell proliferation and growth, its effect on tumor growth is less clear (38,46). Several studies have shown that, in cancer, decreased SERCA2 expression leads to low ER Ca 2ϩ capacity, which then lowers the risk of mitochondrial Ca 2ϩ overload that triggers cell apoptosis (27,40 Cell viability results showing that lung cancer cells exhibit resistance to the cytotoxicity of high concentration of ATP in comparison to normal cells are consistent with published data that showed low (nearly undetectable) expression levels of P2X 7 R in lung cancer cells (20,21,39).…”
Section: Discussionmentioning
confidence: 99%